Actividades orientadas al desarrollo de la motivación para la enseñanza del español como lengua extranjera a adultos extranjeros residentes en Melilla - Mohamed Al-lal, Faysal (2020)
This article proposes to establish a link between motivation and foreign language teaching activities which have personal meaning for the learners and which encourage the group interaction which is very important for the process of foreign language learning. The study tries to find out if this type of activities for learning Spanish are more motivating in learning for adult Moroccan students in an immersion context. The results of the research confirmed our hypothesis that activities with personal significance for learners, on the one hand, motivate students and their increase self-confidence, on the other, help to create a safe and pleasant environment in the classroom